2021
DOI: 10.1111/1756-185x.14236
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of IL‐6, CRP and NT‐proBNP levels in post‐COVID multisystem inflammatory syndrome in children (MISC) and Kawasaki disease patients

Abstract: Background Post‐COVID multisystem hyperinflammatory syndrome in children (MISC) has clinical and laboratory similarities with Kawasaki disease (KD). Inflammatory markers like C‐reactive protein (CRP), interleukin 6 (IL6) as well as N‐terminal probrain natriuretic peptide (NT‐proBNP) are elevated in both. This study attempts a comparative analysis of the 3 markers in an attempt at early differentiation for planning appropriate management. Methodology This analytical stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 14 publications
(13 reference statements)
2
25
0
Order By: Relevance
“… 21 , 22 Furthermore, SARS-CoV-2 infection can trigger a cytokine storm; many pro-inflammatory cytokines and chemokines, such as TNF-α, IL-1β, and IL-6, are overproduced, damaging various organs, including those in the cardiovascular system. 23 , 24 Additionally, cardiovascular risk factors, such as hypertension and diabetes, have been reported to be significant in COVID-19 patients and the mortality rate in former studies. 25 , 26 , 27 COVID-19 itself can also induce cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 Furthermore, SARS-CoV-2 infection can trigger a cytokine storm; many pro-inflammatory cytokines and chemokines, such as TNF-α, IL-1β, and IL-6, are overproduced, damaging various organs, including those in the cardiovascular system. 23 , 24 Additionally, cardiovascular risk factors, such as hypertension and diabetes, have been reported to be significant in COVID-19 patients and the mortality rate in former studies. 25 , 26 , 27 COVID-19 itself can also induce cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that NTproBNP is associated with myocardial damage, stress, and fibrosis, and high NTproBNP levels constitute an independent diagnostic criterion for heart failure. However, it is also known that inflammation appears to be associated with natriuretic peptide release [30,31]. Increasing NTproBNP in MIS-C without severe cardiac involvement may be related to the significant inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…Although, in most cases, cardiac dysfunction seems the result of the hyperinflammatory state and the cytokine storm that cause myocardial stunning and perivascular edema, rather than a direct myocyte injury or an immune-mediated viral trigger. The hypothesis is supported by the disproportion between myocardial damage and the relatively low increase in troponin serum level, while there is a direct correlation between the severity of heart involvement and NTproBNP and inflammatory markers [ 10 , 39 ]. Trisha P. et al showed a significant difference in time to recovery of LVEF comparing classic myocarditis and myocarditis linked to MIS-C (70% vs. 93%) and a significant difference in the needed heart failure medications at three months post-discharge (only 2.2% in MIS-C vs. 45% in classic myocarditis).…”
Section: Discussionmentioning
confidence: 99%